2020
DOI: 10.26803/ijlter.19.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Health Professional Students’ Perceptions and Experiences of Remote Learning During the COVID-19 Pandemic

Abstract: This research aims to investigate the learning experiences and anxiety levels of students attending the College of Health and Rehabilitation Sciences (CHRS) at Princess Nourah bint Abdulrahman University (PNU), Saudi Arabia, during the sudden shift to virtual learning in response to COVID-19. A cross-sectional descriptive study was conducted among CHRS students (N = 254). Data was collected using an online questionnaire. Pearson's correlation coefficient was used to investigate the relationships between studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Although students had positive experiences with remote learning, they also had unpleasant ones. For some students, words such as anxious, frustrated, distressed and overwhelmed were used to describe their experiences (Almoayad et al, 2020;Subedi & Subedi, 2020;Wise & Bergner, 2020). Contrary to the claim by Ghazi-Saidi et al, (2020) and Yuan (2021) that engagements improved with ERL, many studies revealed a reduction in engagement levels (JISC, 2021;Parker et al, 2021;Shin & Hickey, 2020;Wise & Bergner, 2020).…”
Section: Negative Experiencesmentioning
confidence: 99%
“…Although students had positive experiences with remote learning, they also had unpleasant ones. For some students, words such as anxious, frustrated, distressed and overwhelmed were used to describe their experiences (Almoayad et al, 2020;Subedi & Subedi, 2020;Wise & Bergner, 2020). Contrary to the claim by Ghazi-Saidi et al, (2020) and Yuan (2021) that engagements improved with ERL, many studies revealed a reduction in engagement levels (JISC, 2021;Parker et al, 2021;Shin & Hickey, 2020;Wise & Bergner, 2020).…”
Section: Negative Experiencesmentioning
confidence: 99%
“…In the current sample, flexibility, improved communication, and greater autonomy of learning were identified by faculty as perceived successes of the ERT pedagogy. Current faculty perceptions parallel the perceptions of health professional students reported by Almoayad et al (2020) where 67% indicated they were more responsible for their learning, 75% reported ERT helped them to become independent learners, and 71% reported being able to work at their own pace as a positive outcome of ERT.…”
Section: Student Learning Successesmentioning
confidence: 70%
“…Therefore, the lack of preparation at both the technical level and the psychological level-as well as concerns about lower grades-could have contributed to this negative perception. Furthermore, the overall increase in anxiety during the COVID-19 pandemic could also have influenced learning (Almoayad et al, 2020;Cao et al, 2020;Gallagher & Schleyer, 2020;Saddik et al, 2020). Students were also found not to have fully understood e-learning course material, marking a significant difference from instructors' perception.…”
Section: Discussionmentioning
confidence: 99%